Perceptions of the importance of philanthropy according to the classification of generations based on Beresford Research - Endro Tri Susdarwono; S. Thoriqul Huda (Center for Islamic Economics and Development Studies [P3EI], 2023)
Purpose – This study aims to describe the perception of the importance of philanthropy in today's difficult times according to the classification of generations based on Beresford. Methodology – The approach in this study uses a mixed methods research type. The research sample included 400 respondents who traveled with their destination in Pemalang Regency from December to January 2023. The sampling technique used random sampling. While the instrument used in this research is a questionnaire. The data analysis technique uses hypothesis testing on signs and independence hypothesis testing through the Khai-Square distribution. Findings – Based on the hypothesis testing steps above, it is stated that for testing the hypothesis on the sign it is concluded that philanthropy as a part of Islamic social finance is important in today's difficult conditions. As for the independence test, it was concluded that there was no influence between the grouping of generations, according to Beresford Research on the importance of philanthropy as a part of Islamic social finance in difficult times.Implications – Philanthropy is a form of programmed social generosity and is aimed at alleviating social problems (such as poverty) in the long term. Originality – The fundamental difference between this study and previous research lies in using data analysis techniques using non-parametric statistical tests. So, it has a more scientific level of testing results.